Design and Validation of Wireless Priority Service for VoLTE over IMS in Emergency Communication Networks (International Journal of Engineering and Computer Science, 2025)
This article presents a comprehensive technical and operational evaluation of the Wireless Priority Service (WPS) deployed over Voice over LTE (VoLTE) within the IP Multimedia Subsystem (IMS) architecture. The study was conducted through a structured Captive Office Test (COT) environment, simulating high-load and degraded network conditions to validate the resilience and responsiveness of WPS-enabled infrastructure. Central to this implementation is the Resource Priority Header (RPH), which enables real-time signaling-based prioritization based on Service Priority Level (SPL) and Extended Priority (EP) values. The analysis encompasses core IMS components—P-CSCF, I/S-CSCF, and TAS—each of which was instrumented for namespace validation, overload resilience, and accurate policy enforcement. The study confirms that the WPS solution effectively prioritizes NS/EP traffic, sustains high call completion rates under congestion, and adheres to stringent latency targets, while enforcing security and namespace integrity. This article further highlights the technical mechanisms that ensure deterministic priority signaling, the system's adaptability through dynamic profile management, and its robustness in filtering malformed signal ultimately demonstrating readiness for real-world emergency telecommunications scenarios.